2012
DOI: 10.1063/1.3688034
|View full text |Cite
|
Sign up to set email alerts
|

Engineering enhanced thermoelectric properties in zigzag graphene nanoribbons

Abstract: We theoretically investigate the thermoelectric properties of zigzag graphene nanoribbons in the presence of extended line defects, substrate impurities and edge roughness along the nanoribbon's length. A nearest-neighbor tight-binding model for the electronic structure and a fourth nearestneighbor force constant model for the phonon bandstructure are used. For transport we employ quantum mechanical non-equilibrium Green's function simulations. Starting from the pristine zigzag nanoribbon structure that exhibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 41 publications
3
60
0
2
Order By: Relevance
“…Two orders of magnitude reduction in thermal conductivity has been reported for several low-dimensional materials due to roughness compared to the pristine materials, which significantly improve their thermoelectric properties [61,62,14]. Specifically, with regard to GNRs, studies concluded that edge roughness in GNRs can indeed reduce the thermal conductivity by up to two orders of magnitude, depending on the assumptions made about the roughness amplitude and the autocorrelation length.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two orders of magnitude reduction in thermal conductivity has been reported for several low-dimensional materials due to roughness compared to the pristine materials, which significantly improve their thermoelectric properties [61,62,14]. Specifically, with regard to GNRs, studies concluded that edge roughness in GNRs can indeed reduce the thermal conductivity by up to two orders of magnitude, depending on the assumptions made about the roughness amplitude and the autocorrelation length.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have shown that the transports properties of low-dimensional systems are significantly degraded by the introduction of scattering centers and localized states [9,10,22,14,23,24,25]. In the case of electronic transport, even a small degree of disorder can drastically reduce the electronic conductivity (especially in AGNRs rather than ZGNRs), even driving carriers into the localization regime and introduce 'effective' transmission bandgaps [15,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent theoretical works even suggest values up to ~6000 W/mK, with a large proportion of phonon mean-free-paths beyond 10μm [41][42][43]. Previous works indicated that under certain conditions, GNRbased channels could provide very high thermoelectric performance as well [44,45]. In addition, GNRs represent the most realistic 1D system available, and studies on this provide fundamental understanding on heat phonon in purely 1D systems.…”
Section: Introductionmentioning
confidence: 99%